A REVIEW OF ANTIFOULING BIOCIDES CONTAMINATIONS IN INDONESIA, MALAYSIA, THAILAND AND VIETNAM - Harino, Hiroya; Yatsuzuka, Emi; Arifin, Zainal; Rumengan, Inneke F. M.; Ismail, Ahmad; Wattayakorn, Gullaya; Inoue, Koji (Marine Research in Indonesia, 2013)
The concentrations and the distribution of organotin (OT) compounds and booster biocides in sediment and biological samples from Indonesia, Malaysia, Thailand and Vietnam are reviewed. Basically, the concentrations of tributyltin (TBT) in these countries were within the levels that have been reported in developed countries. However, the concentrations of triphenyltin (TPT) and booster biocides were lower than the reported values. Concerning the spatial distribution of antifouling biocides, higher concentrations of OTs were detected in the industrial area and fishing ports. Among ASEAN countries, the highest concentrations of TBT and TPT were observed in Bitung, Indonesia, where many ships from Southeast Asia visit and is moored in the port. The ratio of detected alternative biocide differed from country to country. Especially, many booster biocides were detected and their concentrations were high in Vietnam.